The Constitutional Court's Authority to Review Government Regulations in Lieu of Law (Perppu) from the Perspective of Separation of Powers - Muhammad Febri Eka Saputra; Nadya Fransiska; Nanda Ariadi; Taufiq Hidayat; Rais Jamhary (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
The Constitutional Court (Mahkamah Konstitusi/MK), as the guardian of the Constitution, plays a crucial role in reviewing the constitutionality of legal norms, including Government Regulations in Lieu of Law (Perppu). Although Article 24C paragraph (1) of the 1945 Constitution normatively mentions only “laws” (undang-undang), jurisprudential practice has categorized Perppu as part of statutory law, thus allowing its constitutionality to be reviewed. This study aims to examine the Constitutional Court's authority to review Perppu from the perspective of the theory of separation of powers, while also critically assessing its implications for the stability of Indonesia’s constitutional system. The research method employed is a normative juridical approach with qualitative analysis based on literature review, supported by secondary data including Constitutional Court decisions, statutory regulations, and academic literature. The findings indicate that the Court's authority to review Perppu opens up space for checks and balances on executive power. However, it also carries the potential for disharmony among branches of state power and biased interpretations of the condition of “compelling urgency.”The study concludes that while the Constitutional Court legally holds the legitimacy to review Perppu, clearer juridical boundaries are needed to prevent disproportionate expansion of its authority. This research contributes to the discourse on constitutional law reform in Indonesia by upholding constitutional supremacy and maintaining the balance of powers.